2003
DOI: 10.4141/a03-012
|View full text |Cite
|
Sign up to set email alerts
|

Daily variation in the udder surface temperature of dairy cows measured by infrared thermography: Potential for mastitis detection

Abstract: The daily and within-day variation in udder temperature was monitored in dairy cows (n = 10) using infrared thermography (IRT). The initial assessment and prediction of udder surface temperature variation would hopefully form the basis for future development of an early detection method for mastitis. Our initial objective was to determine the magnitude and pattern of udder temperature variation. To accomplish this, we measured daily fluctuations in udder temperature and the influence of environmental factors u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
136
4
11

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(165 citation statements)
references
References 10 publications
(14 reference statements)
14
136
4
11
Order By: Relevance
“…The use of IR technology to measure the udder temperature has resulted in more controversial results. Schutz and Bewley (2009) did not validate this method unlike Berry et al (2003) and Kunc et al (2007) who found interest of udder surface infrared thermography for mastitis detection. These outcomes are comparable with those obtained for the early detection of leg injuries or lameness in horses or cattle, in which the studies' conclusions diverged.…”
Section: Temperature Measurement With Non Invasive -No Contact Sensorsmentioning
confidence: 99%
See 3 more Smart Citations
“…The use of IR technology to measure the udder temperature has resulted in more controversial results. Schutz and Bewley (2009) did not validate this method unlike Berry et al (2003) and Kunc et al (2007) who found interest of udder surface infrared thermography for mastitis detection. These outcomes are comparable with those obtained for the early detection of leg injuries or lameness in horses or cattle, in which the studies' conclusions diverged.…”
Section: Temperature Measurement With Non Invasive -No Contact Sensorsmentioning
confidence: 99%
“…Montano et al (2009) showed that the IR technique, especially on the extremities of the body, is relevant to the study of feed efficiency of steers. This method is suitable for studies focused on the impact of external conditions on the thermoregulation abilities of cattle, whether the measurements are taken from the skin (Pusta et al, 2012) or the udder (Berry et al, 2003). However, infrared thermography is of limited suitability for evaluating changes in the metabolic rate caused by shearing because this system only measures radiative heat loss, not total nonevaporative heat loss (Autio, 2008;Al-Ramamneh et al, 2011).…”
Section: Temperature Measurement With Non Invasive -No Contact Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thermal cameras have been used for the detection of mastitis; however, these devices were handheld (Berry, et al, 2003, Colak, et al, 2008, Hovinen, et al, 2008, Polat, et al, 2010. While these papers have described an association between mastitis and udder skin temperature, no validated algorithms have been described.…”
Section: Sensor Systems Excluded From This Reviewmentioning
confidence: 99%